A new MAC protocol for wireless ATM networks - Habaebi, Mohamed Hadi; Mohd Ali, Borhanuddin (2000)
In this paper, we study the performance of a new-framed pseudo-Bayesian Aloha algorithm with prioritized adaptive slot assignment algorithm. This algorithm provides faster access to high priority control packets to the uplink frame of the Reservation-TDMA Wireless ATM MAC protocols with minimum effect on the access time of the low priority control packets. The protocol is analyzed with the wireless channel effect and results show that wireless channel improves access time performance for all priority classes.